Distinct Subgroups of Patients With Lung Cancer Receiving Chemotherapy: A Latent Transition Analysis - Li, Nannan; Hou, Lili; Li, Shu (Frontiers in Oncology, 2020)
Objectives: To identify subgroups of patients with lung cancer receiving chemotherapy based on the severity dimension of symptom experience, and to examine changes in membership between these subgroups over time. Methods: Patients who were scheduled to receive chemotherapy completed the Chinese version of the MD Anderson Symptom Inventory and the revised lung cancer module with a total of 19 symptom items. Data were collected at three time points: two weeks before chemotherapy (T1), chemotherapy cycle 1 (T2), and chemotherapy cycle 3 or above (T3). The latent profile analysis (LPA) and latent transition analysis (LTA) were used to identify underlying subgroups and describe changes in subgroup membership over time. Results: From the total sample (N=195), 160 patients completed the symptom assessment at T1, T2, and T3. Two distinct latent symptom profiles of patients could be identified at T1, T2, and T3, which were classified as “Mild” and “Moderate-Severe” profiles. From T1 to T2 and T3, membership in the Mild profile were more likely to move to the Moderate-Severe profile. Chemotherapy protocols, prior surgery treatment and level of education can predict the transitions. Conclusions: Results provide a better understanding of the patient's different symptom experiences and characteristics. These could help clinicians to anticipate symptom patterns and develop interventions in lung cancer patients who were scheduled to receive chemotherapy for the first time.